Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Asuransi Syariah di AJS Bumiputera 1912 Kantor Wilayah Medan - Aprilia, Dita; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
The movement of Islamic insurance growth as one of an Islamic finance instruments is not as fast as the growth of Islamic banking. Nevertheless, it shows a significance growth wether in the world or Indonesia. In the debate over the legal status of insurance, the insurance based on mutual help and free of ribÃ¢ can be an alternative for those who want a lawful economic transactions. The increasing public appreaciation of the Islamic economic system allows the growth of Islamic insurance in the future rapidly.